Wide-Band Electromagnetic Radiation Shielding Construction Based on Pseudooval Scattering Elements for Information Protection Against Leakage Via Electromagnetic Channel - S. E. Savanovich; T. V. Borbotko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The paper considers the results of a study of the influence of the relative position of moisture-containing pseudooval scattering elements with linear dimensions of 10…20, 2…4, 1…4 and 1…2 mm on the electromagnetic radiation reflection coefficients values of the electromagnetic radiation shielding structures, including these elements, and the effective scattering surface of the ground objects, on the surface of which the indicated structures are fixed or applied. Placement of three- or two-layer structures formed on the basis of pseudooval elements with linear dimensions of 2...4, 1...4, 1...2 mm, between two monolayers made on the basis of elements with dimensions of 10...20 mm, leads to the decrease up to –17,6 dB of the electromagnetic radiation reflection coefficients values in the frequency range of 2–12 GHz of the electromagnetic radiation shielding structures, including these elements. The values of the effective scattering surface of ground objects, on the surface of which the indicated electromagnetic radiation shielding structures are located, vary within 0,08...11,80 m2, which is the reason of a significant difficulty in intercepting information about the location and characteristics of ground objects by means of technical intelligence in the frequency range of their operation.